Feasibility study of Songao's low carbon town planning, China - Cheshmehzangi, Ali (Elsevier, 2017)
For the past two decades, low-carbon planning has been one of the main energy planning topics of research at both city and district scales. The attention has for long been on energy consumption reduction by alternative means (such as renewable energies), smart grid systems and measures of CO2 emission reductions and climate change mitigation and adaptation. For developing countries like China, achieving these in a short period is a challenging task. For low carbon planning, there are measures of sustainability, mainly environmental, that can be considered at three scales of ‘target plan’, ‘masterplan’ and ‘construction phase (or implementation)’; some of which are purely focused on energy sector and achieving low-carbon built environments. In here, some of these are studied as part of a feasibility study of a small-scale low carbon town planning case study in Zhejiang Province, East China. This paper is based on a research case study and is divided in to three sections, case study introduction, case study analysis, results and discussions. The conclusions are made based on outcomes of the conducted feasibility study for the case of Songao's low carbon town planning. More importantly, this study highlights the importance of feasibility study for low carbon planning projects and also argues in favour of pre-assessment case of research prior to planning and implementation phase.